Antiperinuclear factor and keratin antibodies in rheumatoid arthritis. Issue 3 (June 1981) - Johnson, G D; Carvalho, A; Holborow, E J; Goddard, D H; Russell, G
Abstract : Tests for antiperinuclear factor (APF) demonstrable by indirect immunofluorescence (IF) on smears of human buccal mucosal cells and for antibodies to keratin (AKA) detected on cryostat sections of rat oesophagus were performed on serum from 102 cases of rheumatoid arthritis (RA) and 117 controls. APF was detected in 92% of the cases of RA; positive tests obtained with non-RA sera were generally weaker than those given by the RA group, and the antibody in both RA and non-RA serum was predominantly IgG class. The difficulty in obtaining suitable substrate material previously reported was confirmed, and only 2 satisfactory donors were identified among 27 individuals tested. The incidence of keratin antibodies detected was found to be related to the site from which the tissue was taken; low oesophagus provided the best discrimination between RA and controls (51% and 5% positive respectively), and cardia of the stomach gave the highest incidence of staining in all groups. A laminar staining pattern was seen with most positive sera, but occasionally the keratinised layer was diffusely stained. The presence of AKA showed a marked correlation with both IgM rheumatoid factor and increased Clq binding in RA, but APF did not.